Cytotoxicity of auricularia polytricha and pleurotus ostreatus var. florida ethanol extracts on human cancer cell lines - Dayrit, Judy Vince Rana (Animo Repository, 2024)
Cancer arises from a multitude of genetic alterations, leading to a spectrum of clinical manifestations that pose a challenge to the global healthcare system. In recent years, there has been a growing trend in the exploration of alternative approaches that leverage the potential of mushrooms as anticancer treatments. Therefore, this study sought to evaluate the cytotoxic potential of crude ethanolic extracts derived from the mushrooms Auricularia polytricha and Pleurotus ostreatus var. florida against human and cancer cell lines using the PrestoBlue™ cytotoxicity assay. The extraction of polar and non-polar compounds from A. polytricha and P. ostreatus var. florida was performed using ethanol. The crude ethanolic extracts were subsequently tested for their cytotoxicity on pancreatic adenocarcinoma (BxPC-3), lung small cell carcinoma (H69PR), and normal liver epithelial (THLE-3) cell lines, which were exposed for 72 hours to two-fold serial dilutions of the extracts having a concentration range of 15.625 to 2000 µg/mL. Zeocin™ served as the positive control. The absorbances of the culture plates were measured at 570 nm and 600 nm, and their cytotoxicity indices were determined to calculate the half-maximal inhibitory concentration (IC50) of the extracts on the human cell lines. Zeocin™ exhibited cytotoxic activity against all the cell lines, with IC50 values of 585.4 μg/mL, 151.4 μg/mL, and 377.5 μg/mL for BxPC-3, H69PR, and THLE-3, respectively. Contrastingly, both mushroom extracts had IC50 values greater than 2,000 µg/mL, which was the highest concentration tested. While the current findings may not indicate robust cytotoxic effects, this does not preclude the potential for these treatments to possess cytotoxic activity.